PENGARUH PROBLEM-BASED LEARNING BERBANTUAN MULTIMEDIA AUGMENTED REALITY TERHADAP KETERAMPILAN BERPIKIR KRITIS SISWA MATERI BUMI BERUBAH KELAS V DI SDN GORDA 2 - Elin Novita; Diana Ayu Rostikawati; Sohri Ramadhan Alfikrii (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
The limitations of critical thinking abilities students form the basis of this research, which has effects on their learning goals. The study's objective is to enhance pupils' critical thinking abilities via a multimedia-assisted augmented reality problem-based learning model. This experimental study employs A Two-Group Pre-test and also Post-test Design. The techniques of data collection utilize a critical thinking skills test consisting of five essay-type questions. Data analysis is conducted using prerequisite tests, namely normality and homogeneity tests, with hypotheses tested using the Mann-Whitney U test as like the n-gain score exam. The results of this investigation demonstrate that there is found such an impact of using problem-based learning assisted by augmented reality multimedia toward students' skills of critical thinking, and There has been progress in pupils' capacity for critical thought. In the class that is being experimented with, the improvement falls into the moderate to high category, but the control group's average n-gain score group only reaches the low to moderate category.